1997
DOI: 10.1002/(sici)1096-8628(19970711)71:1<1::aid-ajmg1>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Sex chromosome markers: Characterization using fluorescence in situ hybridization and review of the literature

Abstract: Fluorescence in situ hybridization (FISH) using biotin labeled X- and Y-chromosome DNA probes was utilized in the analysis of 23 sex chromosome-derived markers. Specimens were obtained through prenatal diagnosis, because of a presumptive diagnosis of Ullrich-Turner syndrome, mental retardation, and minor anomalies or ambiguous genitalia; three were spontaneous abortuses. Twelve markers were derived from the X chromosome and eleven from the Y chromosome; this demonstrates successfully the value and necessity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 53 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…Similarly, the specific detection of male cells in a male/ female epithelial cell mixture, for example male cells under female fingernails or male saliva on female skin, could be of real advantage. Therefore, we used a staining method that detects all cells carrying a Y-chromosome (Schwarz et al 1997) with a digoxigenin labelled chromosome Y cocktail probe from Q Biogen (Q Biogen, Illkirch, France). One Y-specific probe in this cocktail hybridises to multicopy alphoid DNA located at the centromere, a second probe in this cocktail hybridises to short repeated satellites located in the percentric heterochromatin of human chromosome Y.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the specific detection of male cells in a male/ female epithelial cell mixture, for example male cells under female fingernails or male saliva on female skin, could be of real advantage. Therefore, we used a staining method that detects all cells carrying a Y-chromosome (Schwarz et al 1997) with a digoxigenin labelled chromosome Y cocktail probe from Q Biogen (Q Biogen, Illkirch, France). One Y-specific probe in this cocktail hybridises to multicopy alphoid DNA located at the centromere, a second probe in this cocktail hybridises to short repeated satellites located in the percentric heterochromatin of human chromosome Y.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, undertaking cell culture is time consuming, resulting in a reporting time of nearly 2 weeks. Compared with traditional karyotyping, fluorescence in situ hybridization (FISH) does not need cultured cells and results can be obtained in 24–48 h . Nevertheless, the labor intensity, subjective factors as well as unavailability of a high‐throughput system and the high‐testing cost, restricts the popularity of FISH.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical importance of establishing the origin of such marker chromosomes, especially for establishing risks associated with Y‐derived marker chromosomes and gonadal malignancy, has been well documented [3]. It has also been suggested that milder UTS phenotypes are associated with Y‐derived marker chromosomes [4], whereas atypical or severe UTS phenotypes, which may include mental retardation, are more commonly associated with the presence of X‐derived marker chromosomes [5]. To our knowledge, the origin of marker chromosomes in cases ascertained by a presumptive UTS diagnosis and/or cytogenetic findings of sex chromosome loss have always been identified as being either from the X or Y chromosome [4,6].…”
mentioning
confidence: 99%
“…Fluorescence in situ hybridization (FISH) techniques have proven to be some of the most effective techniques for determining the origin of marker chromosomes [4]. However, establishing the chromosomal origin of such marker chromosomes alone is not sufficient to explain the manifestation of a severe or atypical UTS phenotype.…”
mentioning
confidence: 99%